Knowledge of, and attitude to, hormone replacement therapy and menopause among mid-aged New Zealand women : thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Breheny, Mary (Massey University, 1999)
The use of Hormone Replacement Therapy (HRT) by women at menopause is increasing in New Zealand, although there are controversies and confusion surrounding its prescription and efficacy. There has been very little research carried out in New Zealand regarding the variables that impact on HRT use by women, and the attitudes and knowledge of women regarding HRT use. To address this, a survey of 495 mid-aged women, randomly selected from the electoral roll was carried out. The survey measured demographic variables, knowledge of HRT, attitudes to HRT and menopause, and health variables.This study found that knowledge of HRT was high, however, many New Zealand women reported reasons for HRT use that are not empirically supported. This study also found that attitudes to HRT and menopause are important predictors of HRT use, possibly more important than health variables. The importance of attitudes in predicting HRT use needs further clarification to allow the promotion of appropriate information to inform mid-aged women's HRT decision making.
Keywords: Menopause; Hormone Replacement Therapy; Middle-aged women